(untitled) (Research, Society and Development, 2021)
The Basic Education Movement –MEB, in the Sertão do Seridó, presented its literacy proposal through radio schools. The Rural Radio of Caicó was the educational space used for the development of MEB actions in the sertão sertão region. The objective of this work is to present the concept of awareness that is referenced in the documentation for the elaboration of the MEB, such as the report that forwards publications on the development of the MEB between the years 1961 to 1966. The work of Paulo Freire will serve as theoretical analysis. The documentation of the Basic Education Movement is under the custody of LABORDOC (Historical Documentation Laboratory of CERES/UFRN) and its trajectory from 1960 to 1980, in the city of Caicó. We also present as a theoretical proposal the work of Fávero. The methodology applied will be through the analysis of the schedules of radio programs prepared by the teachers/announcers and the reports of the Basic Education Movement, carried out during the first years of the MEB’s operations in Brazil. Analyzing the concept of awareness through the grid of programs broadcast by Rádio Rural in the 1960s to 1980s allows us to observe which dynamics are presented under the influence of the concept of awareness in these programs. Programs that present themes such as: popular health, politicization, evangelization, education, introduces us to the pedagogy used to eradicate illiteracy in the rural population of Seridó, precisely in the city of Caicó.